2020
DOI: 10.1371/journal.pone.0234707
|View full text |Cite
|
Sign up to set email alerts
|

miR-410-3p is induced by vemurafenib via ER stress and contributes to resistance to BRAF inhibitor in melanoma

Abstract: Despite significant development of melanoma therapies, death rates remain high. Micro-RNAs, controlling posttranscriptionally gene expression, play role in development of resistance to BRAF inhibitors. The aim of the study was to assess the role of miR-410-3p in response to vemurafenib-BRAF inhibitor. FFPE tissue samples of 12 primary nodular melanomas were analyzed. With the use of Laser Capture Microdissection, parts of tumor, transient tissue, and adjacent healthy tissue were separated. In vitro experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
(82 reference statements)
0
19
0
Order By: Relevance
“…Significantly, Tan et al ( Tan et al, 2018 ) found that miR-146a induces cisplatin resistance in lung cancer cells by binding to CHOP 3′UTR to inhibit CHOP ( Figure 1 ). Furthermore, another study indicated ( Grzywa et al, 2020 ) that vemurafenib promotes the expression of miR-410-3p by inducing 12 transcription factors downstream of ERS in melanoma. The overexpression of miR-410-3p results in the transformation of melanoma cells into an invasive phenotype, thereby causing their resistance to vemurafenib ( Grzywa et al, 2020 ).…”
Section: Intrinsic Drug-induced Ers and Drug Resistance In Solid Tumorsmentioning
confidence: 99%
“…Significantly, Tan et al ( Tan et al, 2018 ) found that miR-146a induces cisplatin resistance in lung cancer cells by binding to CHOP 3′UTR to inhibit CHOP ( Figure 1 ). Furthermore, another study indicated ( Grzywa et al, 2020 ) that vemurafenib promotes the expression of miR-410-3p by inducing 12 transcription factors downstream of ERS in melanoma. The overexpression of miR-410-3p results in the transformation of melanoma cells into an invasive phenotype, thereby causing their resistance to vemurafenib ( Grzywa et al, 2020 ).…”
Section: Intrinsic Drug-induced Ers and Drug Resistance In Solid Tumorsmentioning
confidence: 99%
“…Recent studies showed miRNAs may serve as diagnostic and prognostic biomarkers in different cancers (Rapado-Gonzalez et al 2019 ; Delangle et al 2019 ; Butz and Patocs 2019 ; Bhat et al 2019 ). Importantly, miRNAs can be detected in formalin-fixed tissues (FFPE), therefore, they may be potentially an extension of conventional histopathological diagnosis (Klopfleisch et al 2011 ; Grzywa et al 2020 ). Numerous studies evaluating miRNA expression in PC led to inconclusive results possibly due to the highly heterogeneous structure of the tumor (Yadav et al 2018 ; Grzywa et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic regulation of ER stress is also of importance when considering disease therapy. An accumulating body of evidence demonstrates the regulation of ER stress by ncRNAs mediators such as miRNAs, lncRNAs, and circRNAs [ 280 , 281 , 282 , 283 ]. Various interactions between ncRNAs and ER stress mediators have already been identified in different types of cancers [ 284 , 285 ].…”
Section: Discussionmentioning
confidence: 99%